Expanding Environmental Health Literacy—A Focus on Water Quality and Tribal Lands. Issue 3 (4th March 2019) - Simonds, Vanessa W.; Margetts, Miranda; Rudd, Rima E.
Abstract : Environmental health literacy (EHL), an evolving concept, has potential for significant public health impact. However, complex skills are needed to access and use information, to study and document hazards, to link findings to health outcomes, and to understand the complexities of regulations and laws needed to take efficacious action. Because water issues are creating headlines world-wide, we draw from several water-related cases on American Indian tribal lands to examine some of the complexities associated with building needed skills, obtaining accessible information, and navigating the layers of laws and regulations that enable or inhibit efficacious action. Each case highlights the importance of partnerships, skill building, and collaborative action to redress environmental assaults. For our analysis, we draw from and expand upon Nutbeam's typology of health literacy which includes functional, interactive, and critical stages to derive lessons from each of the EHL cases. Community partnerships engaging in EHL efforts still face many challenges, including enhancing skills for community members as well as professionals, clarifying scientific processes and findings, articulating and respecting cultural practices and needs, and translating policies and laws for community accessibility and collaborative action.